Single- and multi-piece manuscripts in early imperial China: on the background and significance of a terminological distinction - Staack, Thies (Early China, 2018)
Received and excavated sources from early imperial China employ various terms for pieces of bamboo or wood that served as writing support. In many cases, neither the exact meanings nor diachronic differences in usage of these terms are sufficiently clear. What kinds of concrete objects the terms actually referred to in a certain period accordingly turns out to be quite an intricate question. This article focuses on the terms du 牘 and die 牒, which not only occur most frequently in the sources, but can also be considered as a complementary pair. Investigating differences in form and function that can be gathered from the way the terms are employed in both administrative documents and legal prescriptions of the Qin and Han period (including a newly published Qin ordinance) it argues that du and die were connected to two conceptually different types of manuscripts, namely single- and multi-piece manuscripts. It shows that these two types also entailed differences in how the manuscripts were kept for storage and transport, which were likewise reflected by special terminology. Finally, it proposes that the increasing use of multi-piece manuscripts instead of single-piece ones, especially since the time of Emperor Wu of Han 漢武帝 (r. 141-87 b.c.e.), probably had both pragmatic and economic reasons, which fit well into the setting of a gradually consolidating empire with an ever-growing volume of bureaucratic record keeping., 秦漢時期的傳世和出土資料，記載了不少與用作書寫載體的竹或木片相關的術語。很多時候，它們用法上的確切含義以及歷時性差異，皆未得到充分了解。究竟這些術語在特定時間內，指涉哪些具體事物，成為一個複雜的問題。本文聚焦於「牘」與「牒」，不但由於這兩個詞在資料裏最常出現，還因為它們可被視作互補的一對。爬梳行政文書和法律規範（包括一條新見的秦令）中「牘」和「牒」在形制和功能方面的差異後，本文認為「牘」和「牒」實際上連繫着兩種不同概念的寫本，即單獨簡和編冊簡。本文的分析又顯示，這兩種寫本也意味着儲藏方式的區別，其同樣反映在特殊的術語上。最後，本文提出漢代（特別從漢武帝時起）編冊簡使用之所以日益增加，可能出於實用和經濟原因，這也符合當時漢帝國日漸穩固、官僚系統簿記數量不斷增加的情況。